1982
DOI: 10.3109/00365528209181035
|View full text |Cite
|
Sign up to set email alerts
|

Virus Antibodies in the Serum of Patients with Liver Disease

Abstract: Two hundred and twenty-six patients suspected of having liver disease were examined clinically, by a liver biopsy and laboratory test, according to a prospective scheme. Blood samples obtained just before the liver biopsy were coded and subsequently examined blindly, using the complement fixation test (CFT). The antigens were influenza A and B viruses, parainfluenza 1, 2, and 3, respiratory syncytial viruses, varicella, morbilli, cytomegalo and herpes simplex viruses. The sera were also examined by the CFT aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…[45][46][47] In the past, signifi cant elevated titers of antibodies against rubella have been detected in patients with chronic persistent hepatitis, chronic active hepatitis, and occasionally in acute hepatitis. [45][46][47] More recently Kalvenes et al 48 demonstrated a high antibody response to rubella in active autoimmune chronic hepatitis patients, using three distinct antigen-antibody systems, illustrating an enhanced response to rubella structural proteins in these patients. But with the use of radioimmunoprecipitation assays (RIPA), rubella antibody titers were not increased in PBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] In the past, signifi cant elevated titers of antibodies against rubella have been detected in patients with chronic persistent hepatitis, chronic active hepatitis, and occasionally in acute hepatitis. [45][46][47] More recently Kalvenes et al 48 demonstrated a high antibody response to rubella in active autoimmune chronic hepatitis patients, using three distinct antigen-antibody systems, illustrating an enhanced response to rubella structural proteins in these patients. But with the use of radioimmunoprecipitation assays (RIPA), rubella antibody titers were not increased in PBC patients.…”
Section: Discussionmentioning
confidence: 99%